An Overview of Institutional Experience of General Surgeons of Laparoscopic Splenectomy in Khyber Teaching Hospital, Peshawar - Ahmad Zarka, Mohammad Zarin, Khalid Furqan, Khan Shahzeb (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: An Overview of Institutional Experience of General Surgeons of Laparoscopic Splenectomy in Khyber teaching hospital, Peshawar Methodology: A descriptive KAP (knowledge attitude and practice) study was conducted in Khyber teaching hospital (KTH) from February 2021 to March 2021. Experience of only those General Surgeons, who have performed both Open and Laparoscopic Splenectomies was included in the study. Data was collected through a self –administered questionnaire and a total of eleven faculty members of our surgical department qualified to be a part of the study. Results: Eleven consultants of our surgical department qualified to be a part of the study. In the category of intra-operative complications, 8(72.7%) designated it as an optimum method of hemostasis, 9(81.8%) experienced no iatrogenic injury, 7(63.6%) never converted laparoscopic to an open splenectomy. Among post-operative complications, hemorrhage was witnessed only by 3(27.3%) while 8(72.7%) never had a patient with the mentioned complication. Wound Infection, post-operative ileus and post splenectomy sepsis were experienced only by 2(18.2%) participants and 9(81.8%) had not received patients with such complications. 8(72.7%) surgeons favored use of this technique for easy identification and removal of accessory spleen. 7(63.6%) participants had a consensus on it being a safe and easy method for specimen retrieval. In post-operative recovery, 9(81.8%) patients had a hospital stay of 2 days while 10(90.9%) observed an early activity resumption. A total of 8(72.7%) General Surgeons preferred Laparoscopic Splenectomy. Conclusion: The study showed that majority of the surgeons preferred use of Laparoscopic Splenectomy.